2008
DOI: 10.1136/bjsm.2008.047761
|View full text |Cite
|
Sign up to set email alerts
|

Running in new and worn shoes: a comparison of three types of cushioning footwear

Abstract: As shoe cushioning capability decreases, runners modify their patterns to maintain constant external loads. The adaptation strategies to shoe degradation were unaffected by different cushioning technologies, suggesting runners should choose shoes for reasons other than cushioning technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 36 publications
2
47
0
3
Order By: Relevance
“…Less striking but nevertheless interesting observations18 revealed that midsole hardness had an acute effect on running kinematics during the stance phase, especially in the sagittal plane. Biomechanical adaptations have also been observed in runners who gradually wore out their running shoes and modified their pattern so as to maintain constant external loads 19. Although not analysed here, it is possible that adaptations of running style cancelled out the differences in shock-absorbing characteristics of the shoes used by our participants and thus the RRI risk.…”
Section: Discussionmentioning
confidence: 86%
“…Less striking but nevertheless interesting observations18 revealed that midsole hardness had an acute effect on running kinematics during the stance phase, especially in the sagittal plane. Biomechanical adaptations have also been observed in runners who gradually wore out their running shoes and modified their pattern so as to maintain constant external loads 19. Although not analysed here, it is possible that adaptations of running style cancelled out the differences in shock-absorbing characteristics of the shoes used by our participants and thus the RRI risk.…”
Section: Discussionmentioning
confidence: 86%
“…Shoe age has been postulated as a cause for injuries [6]. The theory is that the cushioning properties of shoes reduce with increasing mileage [10]. Studies show that incorrectly fitting footwear is strongly associated with forefoot pathology and foot pain [3,11].…”
Section: Resultsmentioning
confidence: 99%
“…The only study comparing new and worn shoes with regards to cushioning concluded that worn shoes caused increased stance phase and kinematic adaptations by the runner when shoe cushioning reduces [10]. The consensus is that worn-out running shoes offer less protection, as mentioned earlier, causing high plantar pressures [10]. This may directly or indirectly cause musculoskeletal problems.…”
Section: Resultsmentioning
confidence: 99%
“…Inappropriate shoe that fails to attenuate excessive shock on the human body has been identified as one risk factor for acute or fatigue overstress injuries [911]. Appropriate performance footwear should effectively attenuate impact forces generated during various impact activities[12].…”
Section: Introductionmentioning
confidence: 99%
“…In badminton, players often performed powerful and long-distance lunges having more than 40 degrees of the sagittal footstrike angle [7,16,18,19], which is much larger than heel-toe running having about 20 degrees[11]. Due to this unique sagittal footstrike angle and the location of initial contact, changes in heel curvature design of a badminton shoe might alter impact attenuation during lunge movements.…”
Section: Introductionmentioning
confidence: 99%